Stylopsal: the first identified female-produced sex pheromone of strepsiptera - Cvačka, Josef; Jiroš, Pavel; Kalinová, Blanka; Straka, Jakub; Cerná, Kateřina; Šebesta, Petr; Tomčala, Aleš; Vašíčková, Soňa; Jahn, Ullrich; Šobotník, Jan (Journal of chemical ecology, 2012)
A female-produced sex pheromone of Stylops muelleri was identified as an unusually branched saturated aldehyde (9R)-3,5-syn-3,5,9-trimethyldodecanal. We named it stylopsal. Its structure was established by using mass spectrometry, infrared spectroscopy, and organic synthesis of candidate compounds. The synthetic standard of (9R)-3,5-syn-3,5,9-trimethyldodecanal gave identical chromatographic and mass spectrometric data as the natural pheromone and also was active in electroantennographic and behavioral assays. The female fat body lipids contained the corresponding fatty acid, indicating a possible link between lipid metabolism and the pheromone biosynthesis.
Keywords: Sex Attractants; Stereoisomerism; plynová chromatografie s hmotnostně spektrometrickou detekcí; stereoizomerie; Spectrophotometry, Infrared; zvířata; tukové těleso; hmyz; mužské pohlaví; Gas Chromatography-Mass Spectrometry; Fat Body; Sexual Behavior, Animal; spektrofotometrie infračervená; sexuální lákadla; ženské pohlaví; aldehydy; Animals; Insecta; Aldehydes; Male; sexuální chování zvířat; Female